2008
DOI: 10.1177/1753193408090106
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Plain X-Rays in Predicting TFCC Injury after Distal Radial Fractures

Abstract: In this prospective study, the plain X-rays and MRI scans of 60 patients with intraarticular distal radius fractures were examined in random order. MRI evaluation revealed that 27 of the 60 patients (45%) had triangular fibrocartilage lesions. No correlation was found between triangular fibrocartilage injury and the Melone classification system, the presence of an ulnar styloid fracture, comminution of the articular surface of the distal radius, >20 degrees dorsal angulation of the distal radius or subluxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…3,5,12,13 This discrepancy could be explained by the differences between complete and incomplete tears. The previous studies included partial radioulnar ligament tears because the diagnosis was via arthroscopic assessment using indirect means such as probing.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…3,5,12,13 This discrepancy could be explained by the differences between complete and incomplete tears. The previous studies included partial radioulnar ligament tears because the diagnosis was via arthroscopic assessment using indirect means such as probing.…”
Section: Discussionmentioning
confidence: 86%
“…A review of the literature revealed that 21% to 33% of distal radius fractures had an associated radioulnar ligament tear at the ulnar attachment. 3,5,12,13 Previous investigators of distal radius fractures have reported that the fracture pattern, magnitude of fracture displacement, and presence of an ulnar styloid fracture correlate with TFCC injuries. 6,13,14 We proposed that an awareness of independent predictors would be helpful in anticipating the functional outcome because DRUJ instability may contribute to late arthritis and suboptimal clinical outcomes.…”
mentioning
confidence: 99%
“…Because current classification systems of acute distal radius fractures based on pathology have only moderate or poor reproducibility [8,[17][18][19] and because the available series often consider wide ranges of patients age [14,[20][21][22], we designed a new method of analysis using binary and qualitative criteria in a consecutive series of 258 patients from a single centre, treated over a 18-months period, and of whom the preliminary results are presented. The general distribution of our study population did not differ from that of previous large epidemiologic studies of distal radius fractures [23] in that the sex ratio shows a larger proportion of female patients and that women are on average older than men.…”
Section: Discussionmentioning
confidence: 99%
“…When present, they are very important factors of the treatment [9]. Displaced fractures of the base or the tip of the ulnar styloid were recorded since they may be associated with a higher probability of triangular fibrocartilage complex (TFCC) deficiency [14]. Distal radioulnar joint (DRUJ) diastasis, subluxations or dislocations were also included.…”
Section: Associated Druj Lesionsmentioning
confidence: 99%
“…In this injury group, it has been shown that TFCC tears can been detected in up to 80% of patients with displaced fractures. [20][21][22] Deniz et al obtained magnetic resonance imaging (MRI) from 47 consecutive DRF patients treated conservatively with closed reduction and casting. TFCC injury was detected in 24 (51%) of the patients (Type 1A 5, Type 1B 17, Type 1C 1, and 1 complex tear).…”
Section: Nonoperative Treatmentmentioning
confidence: 99%